Allostery without a conformational change? Revisiting the paradigm. (February 2015) - Nussinov, Ruth; Tsai, Chung-Jung
Highlights: Classically, allostery induces a functional switch through a conformational change. Lately numerous studies concluded that allostery takes place through dynamics. Even if no observable conformational change it does not mean no change. Specific functions emerge from specific interactions between complementary shapes. Abstract : Classically, allostery induces a functional switch through a conformational change. However, lately an increasing number of studies concluded that the allostery they observe takes place through sheer dynamics. Here we explain that even if a structural comparison between the active and inactive states does not detect a conformational change, it does not mean that there is no conformational change. We list likely reasons for this lack of observation, including crystallization conditions and crystal effects; one of the states is disordered; the structural comparisons disregard the quaternary protein structure; overlooking synergy effects among allosteric effectors and graded incremental switches and too short molecular dynamics simulations. Specific functions are performed by distinct conformations; they emerge through specific interactions between conformationally selected states.